(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The proposal developed in this paper suggests an inclination towards addressing institutional change, since special emphasis is placed on how institutions have impacted the development of Mexican fiscal federalism, in particular of three states that, due to their fiscal situation, make it possible, comparatively, establish a timely diagnosis of its inherent factors, in order to explain its processes and future horizons. For this reason, the general objective of the work is to identify the increase or decrease of federal transfers to the entities of the State of Mexico, Guanajuato and Tabasco, the comparative method is proposed for the search of empirical references. The results obtained reflect that there is an influence of partisan alignment regarding the distribution of resources, particularly from Branch 33. Among the most important findings derived from the study is that in relation to the resources transferred, in Branch 33, there is constantly in the last eight years an overexercise. However, the state that overexerts these resources with the greatest presence in the period between 2012 and 2018 is the state of Tabasco, with data that averages 7 percent per year.